Still remembering the origins: The continuity of syncretic Islamic practice among the Gumay (Gumai) in South Sumatra, Indonesia. Issue 131 (2nd January 2017) - Sakai, Minako
ABSTRACT: Over the last three decades, the influence of orthodox Islam in contemporary Indonesian society has become increasingly visible. The use of Muslim clothing, Islamic expressions and commodities has become prevalent in the everyday life of Muslims in Indonesia. Along with this change, some prominent localised forms of Islam are being gradually replaced by standard orthodox Islam. However, syncretic Islamic practices continue strongly in some regions in Indonesia. In this article I explore factors enabling syncretic forms of Islamic practice through a case study of the Gumay of South Sumatra. Drawing on a longitudinal ethnographic study of the Gumay people, I argue that the sustained importance of local Islamic authorities and the transmission of Islamic knowledge that are embedded in everyday kinship relations is the key, although school education and other external Islamic authorities are shaping the way Muslim Gumay see what orthodox Islam should be. Also important are the Indonesian government's cultural policies, the political importance of ethnicity, and the popular use of new media as these have played a significant role in keeping such syncretic Islamic practices alive among the younger generations of the Gumay.